Issues of Determining the Legal Nature and Place of the Corporate Contract (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article highlights the issues of corporate governance, ensuring the organization of relations between the participants of the company, their rights, obligations and the procedure for their implementation.